IMPLEMENTASI INOVASI SISTEM MANAJEMEN PELAYANAN TERPADU (SIMYANDU) DALAM PROSES PERIZINAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALANGKA RAYA - Rasan, Febriomico Griando; Sahay, Marvy Ferdian Agusta; Hikmah, Nurul; Mahendra, Alfian Maulana Isa; Jaya, Imanuel (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
SIMYANDU is a service provision system in the licensing sector that is fast, effective and efficient. This research aims to analyze the implementation of SIMYANDU using the theory of Delone & McLean (2003) which states the variables of successful technology implementation, namely information quality, system quality, service quality, usage, user satisfaction and benefits using descriptive qualitative methods. The research results show that the low use of SIMYANDU by the community is due to the lack of socialization and guidance carried out by the Palangka Raya City DPMPTSP so that public knowledge in applying for permits online is still low